Strategi Bersaing Keripik Singkong Cap Gerus Produksi UKM Sumekar Pratiwi Kabupaten Tuban - Mohamad Harisudin Mahfud; Setyowati Setyowati; Nizar Utami (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
This research aim to assess the determinants of success of Cassava Chips Gerus, assess the competitive position of Cassava Chips Gerus, and formulate the alternative strategies for SME Sumekar Pratiwi in order to market their products. The basic method used in this research is descriptive analytic. Subject of this research is determined purposively. The data used in this study are primary and secondary data. This study used Competitive Profile Matrix (CPM) as its analysis data method. The result shows factors that determined the success of cassava chips Gerus brand. Based on CPM analytic, the product of cassava chips Gerus brand (3.116) occupies the second position in comparison to its competitors, namely cassava chips C (2.058) and cassava chips D (1.655). Cassava chips B (3,171) occupies the first position. Alternative competitive strategy that can be applied to the cassava chips Gerus is to promote the brand Gerus brand through sales-force promotion, conduct product positioning to create the image of quality products: that taste more savory, has the most recognized brands, more attractive label design and label information is more informative, and benchmark color, taste of the final product after the meal and set prices quantity discounts to final consumersKey words: Cassava Chips, Competitive Profile Matrix, Competitive Strategy